Manajemen Pembelajaran Akidah Akhlak berbasis Habit Forming di MTsN 2 Jombang - Diva kusuma Firdaus; Nur 'Azah (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Learning management is the teacher's ability to utilize existing resources, through activities to create and develop collaboration, so that learning is created between them to achieve educational goals in the classroom effectively and efficiently. Learning moral beliefs is one of the subjects in which there are values that can be applied in everyday life. Therefore, learning the Aqidah Akhlak is very suitable as a means of forming positive student character and habits. Through Aqidah Akhlak lessons and refraction activities, this is one way of forming positive character and habits, because it contains life values that must be applied in everyday life. The aim of this research is to see how the management of moral teachings is based on habituation. This research is a case study type with descriptive methods. The results of the research explain that the management of moral belief learning must run well, because the management of moral belief learning has a big influence on students' habits.